2013
DOI: 10.1080/19424280.2013.834982
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gender, age, and body mass on dynamic foot shape and foot deformation inchildren and adolescents

Abstract: Purpose: The aim of the present study is to identify influences of gender, age, and body mass on the dynamic foot morphology and foot deformation of maturing feet. Only advancements in scanner technology enable recording of foot morphology during walking. Methods: Static and dynamic foot morphology of 2554 participants (6-16 years) were measured with DynaScan4D. Different foot measures corresponding to measures used in last construction were defined. Influences of gender, age, and body mass were calculated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 59 publications
(77 reference statements)
0
19
0
Order By: Relevance
“…Regarding the roll-over process, most of body weight is already shifted to the forefoot when the toes touch the ground. Thus, it can be assumed that no additional extension takes place and MBL is representative for foot extension (Barisch-Fritz et al, 2014).…”
Section: Analysis Of Scan Data and Statisticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the roll-over process, most of body weight is already shifted to the forefoot when the toes touch the ground. Thus, it can be assumed that no additional extension takes place and MBL is representative for foot extension (Barisch-Fritz et al, 2014).…”
Section: Analysis Of Scan Data and Statisticsmentioning
confidence: 99%
“…The medial point was manually detected for each frame. The reliability of this procedure was determined for static (intra-class correlation coefficient, ICC D 0.978, RMSE D 2.3 mm) and dynamic situations (ICC D 0.992, RMSE D 2.3 mm) ( Barisch-Fritz et al, 2014). Mean values of three dynamic trials were used for calculating foot extension and walking advance.…”
Section: Analysis Of Scan Data and Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…With these growth rates, it seems only logical that the footwear of schoolchildren may become small quickly. Current reviews on the topic emphasize the importance of taking into account the changing morphology of children’s feet, which, along with their high functional demand, must be considered when designing ergonomic footwear [5, 6]. In the same way, some studies have shown that foot shapes differ between populations and genders, and for proper footwear fit, footwear should have enough size varieties to imitate different foot shapes of all humanity [7, 8].…”
Section: Introductionmentioning
confidence: 99%